Improved liquid chromatography combined with pulsed electrochemical detection for the analysis of etimicin sulfate. Issue 8 (April 2016) - Wu, Yuning; Zhao, Wei; Zhu, Xiaoyue; Wang, Fang; Zhang, Mei; Fan, Xialei; Yuan, Yaozuo; Hu, Changqin; Deng, Xiaolan; Adams, Erwin
Abstract : This paper describes an improved liquid chromatography method combined with pulsed electrochemical detection for the analysis of etimicin sulfate. In total, 22 impurities could be separated. A TSK‐GEL C18 column (250 mm × 4.6 mm i.d., 5 μm) is used, and the mobile phase is composed of 40 mL of acetonitrile and 960 mL of an aqueous solution containing trifluoroacetic acid (15 mL/L), pentafluoropropionic acid (500 μL/L), 50% sodium hydroxide (8 mL/L) and sodium sulfate (1.5 g/L). The pH of the aqueous solution is adjusted to 3.5 with 0.8 M sodium hydroxide. The influence of the different chromatographic parameters on the separation was investigated. A quadruple potential‐time waveform was applied to the electrodes of the detection cell. 0.8 M sodium hydroxide was added post column to raise the pH to at least 12 before detection. A central composite experimental design was used to describe the relationship between factors and response values and to establish factorial analysis. Compared to previously published investigations, this improved method shows higher sensitivity, better separation ability and robustness and has been incorporated by the Chinese Pharmacopoeia 2015 for analysis of etimicin sulfate. A number of commercial samples of etimicin sulfate were also analyzed using this method.